Sous l’égide de Minerve et de la science immuable - Olivier Deloignon (Recherches Germaniques)
Under the Aegis of Minerva and the Unchanging Science. Lazarus Zetzner, a Bookseller in Strasbourg and the Publisher of the Chymical WeddingLazarus Zetzner was an important bookseller at the beginning of the 17th century in the Germanic world. He published history books, law books and philosophy books by ancient authors (Marcus Aurelius, Caesar, Stace, Thucydides, Martial, Cicero) as well as contemporary humanists (Pietro Bembo, Erasmus, Turnebus). But he was also very active in the fields of paracelsianism and alchemy, whether it was in Latin or in vernacular. Moreover, he was, along with his heirs, the printer of Johann Valentin Andreae, the main instigator of the Rosicrucian case and in particular of Christian Rosencreutz’ Chymical Wedding, which was published anonymously in 1616 on Conrad Scher’s printing press in Strasbourg. The analysis of the publishing sector of Strasbourg, of Zetzner’s book production and some remarks about material bibliology will enable us to place the Chymical Wedding in its context of production and distribution.